pata nahi answer wrong kyu ara hai LOL [3]
btw euclid i tried wid d same way dat u r telling , but pata nai ans match nai hora
btw vivek wats d source of the question ?
i solved it dis way
aB/C= [- aB/C cosθ] (i ) + [- aB/Csinθ] (j)
(since B moves only along d incline as seen by C )
aC = aC (i )
→ aB = aB/C + aC = [aC - aB/C cosθ] (i ) + [- aB/Csinθ] (j)
aA = aA (j ) [ no i component as no force in x direction )
also , since A never loses contact with B, A has accn only in horizontal direction AS SEEN BY B ,hence a(A/B)y= 0 i.e (aB)y = (aA)y
so aA = [- aB/Csinθ] (j)
now Σ m a x-component= 0
so aC+ aC - aB/C cosθ = 0
aB/C cosθ = 2aC
so aB = - aC (i )+ [- 2aCtanθ] (j) ..........( 1 )
so aA = (aB)y (j ) = [- 2aCtanθ] (j) .........( 2 )
let N1 = normal force of B on C , N2 = normal force between A and B
N1sinθ = maC
mg + N2 - N1cosθ = m( aB )y = 2maCtanθ
mg - N2 = m(aA)y= 2maCtanθ
so 2mg - N1cosθ = 4maCtanθ
2mg = maCcotθ + 4maCtanθ
so , aC = 2gtanθ1+4tan2θ